A New Heuristic Approach for Low-Thrust Spacecraft Trajectory Optimization. Issue 2 (2020) - Coppens, Peter; Hermans, Ben; Vandersteen, Jeroen; Pipeleers, Goele; Patrinos, Panagiotis
Abstract: Electrical propulsion is gaining popularity in the satellite industry. Their high efficiency however comes at the cost of decreased thrust and longer transfer times. As such the interest in solving the large optimization problems associated with these long transfers has re-surged. This paper presents a heuristic approach to solving such low-thrust satellite trajectory optimization problems, based on control law blending and averaging. We derive the nonlinear program resulting from this approach and introduce PANOC, a recent optimization algorithm well suited for optimal control problems. The resulting controller is considerably faster than more classical, non-heuristic approaches, without a significant loss in optimality.